Investigating a role for members of the respiratory tract microbiota in Th17 cell pathogenicity and CNS autoimmunity - Mannion, Jenny (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2022)
The respiratory tract is home to a diverse microbial community whose influence on local and systemic immune responses is only beginning to be appreciated. Increasing reports have linked the airways with the trafficking of myelin-specific T cells in the pre-clinical stages of experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis (MS). Myelin-reactive Th17 cells are important pathogenic effectors in MS and EAE but are innocuous immediately following differentiation. IL-23 driven conversion to an ex-Th17 cell phenotype appears to be a critical step in their acquisition of pathogenic potential, but little is known about the mechanisms that mediate this process. We hypothesize that the airways are a critical site in the immunopathogenesis of EAE, where respiratory tract bacteria express crucial factors that promotes encephalogenicity in Th17 cells. We exposed innate immune cells in vitro and ex vivo to a range of respiratory symbionts and examined IL-23 and related cytokine secretion. In vivo, we colonised the upper respiratory tract of mice with selected bacteria to determine expression of IL-23 and related cytokines in the airways. We transferred myelin-specific Th17 cells to congenic recipient mice exposed to a range of IL-23 inducing human respiratory symbionts and monitored disease severity and T cell trafficking. Disease was exacerbated in mice exposed to the IL-23 inducing Proteobacteria species Moraxella catarrhalis and Klebsiella pneumoniae, but not the Firmicute species Veillonella parvula (commonly associated with healthy human lungs), compared to PBS administered controls. Disease susceptibility was reduced in germ-free mice compared to conventionally housed mice but was partially restored in germ-free mice colonised with K. pneumoniae. In the pre-clinical stages of disease, we found a significant increase in the frequency of GM-CSF + and GM-CSF + IFNγ + double positive donor CD4 T cells in the lungs of mice exposed to M. catarrhalis or K. pneumoniae, compared to V. parvula-exposed mice or PBS controls. We also found elevated expression by donor Th17 cells of key trafficking molecules including CCR6 and CXCR6 in the lungs of these mice. In vitro, dendritic cells exposed to these respiratory bacteria secrete high concentrations of the critical pathogenic cytokine IL-23 and Th17- polarised cells co-cultured with these bacteria-stimulated dendritic cells also displayed a significant increase in GM-CSF and IFNg expression. Our data indicates that exposure to the respiratory symbionts M. catarrhalis and K. pneumoniae promotes expression of key pathogenic molecules in myelin-specific Th17 cells and supports the concept that perturbations in the respiratory microbiota may contribute to the pathophysiology of CNS autoimmune disease.
APPROVED
Keywords: Lung microbiota; CNS autoimmunity; Th17 cell pathogenicity